Concurrent solution and adsorption of hydrocarbons in gas chromatographic columns packed with different loadings of 3- methylsydnone on chromosorb P - Castells, R. C. (1998)
Thermodynamic properties of solution in 3-methylsydnone (3MS) and of adsorption at the nitrogen/3MS interface were gas chromatographically measured for a graup of fifteen hydrocarbons at infinite dilution conditions. Retention voluntes were measured at five temperatures within the range 37-52°C in six columns containing different loadings of 3MS on Chromosorb P AW. Partition and adsorption coejficients were calculated and from their temperature dependence the corresponding enthalpies were obtained, although with considerable error; infinite dilution activity coejficients of the hydrocarbons in the bulk and in the surface phases demonstrated an strong correlation. Bulk activity coefficients in 3MS were very much smaller than those previously measured for the same solutes in formamide (FA) and in ethyleneglycol (EG), and were also smaller than what could be predicted on account of 3MS cohesive energy density as estimated from the quotient a/v13 (cr. surface tensión; v: molar volume). There was not such a large difference between the surface activity coefficients in the three solvents; furthermore, the quotients (surface activity coefficient/bulk activity coefficient) for a given solute in 3MS were twice as large as in FA and about three times larger than in EG. These results make evident the difficulties inherent in the prediction of surface phase properties from those in the bulk, and casi doubts on the pertinency of employing the surface tensión to compare cohesive energy densities of polar solvents with important Chemical dijferences.